1961
DOI: 10.1002/prac.19610130504
|View full text |Cite
|
Sign up to set email alerts
|

Gemischte Xanthogensäureanhydride

Abstract: Es wird die Darstellung von Alkylxanthogen‐phosphorigsäureanhydriden und Dixanthogensäure‐dialkylestern durch Umsetzung von Kalium‐Alkylxanthogenaten mit Chloriden des Phosphors und des Schwefels beschrieben. Die Verbindungen zeigen Sammlerwirkung bei der Flotation sulfidischer Erze.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1965
1965
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Paper chromatography (solvent A) Rf 0.72. Paper electrophoresis (0.05 M phosphate, pH 8) Rd-pT 0.54. Anal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paper chromatography (solvent A) Rf 0.72. Paper electrophoresis (0.05 M phosphate, pH 8) Rd-pT 0.54. Anal.…”
Section: Methodsmentioning
confidence: 99%
“…Soc., 82, 5749 (1960); K. Ogura, T. Nishino, T. Koyama, and S. Seto, ibid., 92, 6036 (1970). (8) Reactions were carried out under a nitrogen atmosphere. Unless indicated otherwise, the isolation of reaction products was accomplished by pouring the mixture into water or saturated brine and extracting thoroughly with the specified solvent.…”
mentioning
confidence: 99%
“…Paper chromatography (solvent A) Rf 0.72. Paper electrophoresis (0.05 M phosphate, pH 8) Rd-pT 0.54. Anal.…”
Section: Methodsmentioning
confidence: 99%
“…Sodium tetrathionate, cyanogen bromide, nitrous acid, and iodine are some of the oxidizing agents currently used. [2][3][4][5] Several studies on the biological activities of this family of compounds have suggested its potential application as antitumoral or antiviral agents, among others. For example, the ability of bisethylxanthogen as an inhibitor of carcinogenesis was proposed by different authors [6][7][8] and its use in the treatment of dermatological infections was reported.…”
Section: Introductionmentioning
confidence: 99%